Differences in Sexual Health Outcomes Between Adolescents in Public Schools and Juvenile Correctional Facilities. (October 2020) - Thompson, Meagan; Davis, Laurel; Pendleton, Virginia; Shlafer, Rebecca
Data from a statewide, anonymous survey were used to test for differences between adolescents' sexual health behaviors and their outcomes across settings. Youth in juvenile correctional facilities (JCFs) were disproportionally male and Black compared to their peers in public schools. Youth in JCFs were significantly more likely than their peers to report that they had ever had sex, used substances prior to last sex, or been involved in a pregnancy. They were less likely to have used condoms or contraception at last sex, or to report having talked with their partners about sexually transmitted infections or birth control. The results highlight the importance of comprehensive sexual health education and access to a reproductive health provider for students in JCFs.